2013
DOI: 10.1016/j.ydbio.2013.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The cytoskeletal protein Zyxin inhibits Shh signaling during the CNS patterning in Xenopus laevis through interaction with the transcription factor Gli1

Abstract: Zyxin is a cytoskeletal protein that controls cell movements by regulating actin filaments assembly, but it can also modulate gene expression owing to its interactions with the proteins involved in signaling cascades. Therefore, identification of proteins that interact with Zyxin in embryonic cells is a promising way to unravel mechanisms responsible for coupling of two major components of embryogenesis: morphogenetic movements and cell differentiation. Now we show that in Xenopus laevis embryos Zyxin can bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…To identify genes directly or indirectly regulated by zyxin, we compared the next-generation sequencing (NGS) transcriptomes of X. laevis embryo neural plates excised together with the underlying mesoderm from wild-type embryos at the midneurula stage and from sibling embryos in which zyxin was downregulated with the anti-sense morpholino (MO) to zyxin mRNA as described in our previous paper (Martynova et al, 2013;Figure 1A). As a result,~200 differentially expressed genes were revealed (with R2-fold difference) (Table S1).…”
Section: Comparison Of the Transcriptomes Of Axial Tissues Of Normal mentioning
confidence: 99%
See 2 more Smart Citations
“…To identify genes directly or indirectly regulated by zyxin, we compared the next-generation sequencing (NGS) transcriptomes of X. laevis embryo neural plates excised together with the underlying mesoderm from wild-type embryos at the midneurula stage and from sibling embryos in which zyxin was downregulated with the anti-sense morpholino (MO) to zyxin mRNA as described in our previous paper (Martynova et al, 2013;Figure 1A). As a result,~200 differentially expressed genes were revealed (with R2-fold difference) (Table S1).…”
Section: Comparison Of the Transcriptomes Of Axial Tissues Of Normal mentioning
confidence: 99%
“…We next attempted to unravel the mechanism by which zyxin controls the stability of pou5f3.3 mRNA based on data from a previous study in which we performed yeast two-hybrid screening (2HS) to find proteins that could interact with zyxin in X. laevis embryos (Martynova et al, 2013). One of the potential protein partners of zyxin was Ybx1, a Y-box transcription factor that can form a ribonucleoprotein (RNP) complex with mRNA, thereby greatly increasing its resistance to degradation (Sommerville and Ladomery, 1996;Evdokimova et al, 2001).…”
Section: Zyxin Interferes With the Formation Of Complexes Between Poumentioning
confidence: 99%
See 1 more Smart Citation
“…Lysates of embryos were prepared as described (Bayramov et al, 2011;Martynova et al, 2013). For immunoprecipitation, aliquots of lysates containing standard amount of tagged protein were mixed with EZview Red ANTI-MycAffinity Gel (Sigma E6654) or EZview Red ANTI-Flag Affinity Gel (Sigma F 2426) and incubated with rotation overnight at4C.…”
Section: Immunoprecipitation and Antibodiesmentioning
confidence: 99%
“…Recently we identified the Xenopus homologue of Zyxin and demonstrated that this protein can bind to the transcription factors Xanf1 and Gli1 and modulate their activity in cells of the CNS (Martynova et al, ). Given these data, we hypothesize that Zyxin may act as a mechanosensitive regulator of gene expression in early CNS development.…”
Section: Molecular Mechanisms Mediating Mechano‐dependent Regulation mentioning
confidence: 99%